Research on Spatial Location of a Spherical 3-RRR Parallel Mechanism - Wang Li (Jixie chuandong)
The quaternion is used to represent the finite rotation of rigid body, and the finite rotation equation of rigid body is obtained. Based on the spherical 3-RRR parallel robot, an angular displacement sensor bracket is added to detect the attitude angle of the moving platform, and the positioning deviation is transformed into a quaternion form. Thus, the robot is applied to the actuator of the spatial positioning problem. Aiming at the large-scale asymptotically stable dynamic quality of the system, the conditions that the angular velocity of the moving platform should satisfy are obtained, and the quaternion differential equation of motion of the moving platform in the positioning process is established. The solution trajectory of the deviation quaternion and the change course of the attitude of the moving platform during the positioning process of the robot are given by an example. The control law applied to the active component is obtained. The simulation results show that the control effect is better.